Podstawowe założenia programu metodyki nauczania literatury jako przedmiotu studiów w szkołach wyższych = The Basic Assumptions of the Program of Literature Didactics as a Subject of Studies in High Schools - Polakowski, Jan (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper frames the fundamental assumptions of the program of literature didactics, based on actual situations existing in modern culture with special reference to its literary communication. Modern didactic trends are considered, which fix the attention on the pupil his way of learning, and motivations of the teacher's activities. Because of the various conceptions, of that subject, the author shetches such a conception assuming the neccesity of research in the mechanisms of the literary work reception as the base of the scientific description of every "receptional strategy"
Keywords: dydaktyka literatury; szkolnictwo wyższe